Exopolysaccharide dispelled by calcium hydroxide with volatile vehicles related to bactericidal effect for root canal medication - Lei Lei; Meiying Shao; Yan Yang; Mengying Mao; Yingming Yang; Tao Hu
ABSTRACT Objective: Enterococcus faecalis is the dominant microbial species responsible for persistent apical periodontitis with ability to deeply penetrate into the dentin. Exopolysaccharides (EPS) contribute to the pathogenicity and antibiotic resistance of E. faecalis. Our aim was to investigate the antimicrobial activity of calcium hydroxide (CH), camphorated parachlorophenol (CMCP), and chlorhexidine (CHX) against E. faecalis in dentinal tubules. Material and Methods: Decoronated single-canal human teeth and semicylindrical dentin blocks were incubated with E. faecalis for 3 weeks. Samples were randomly assigned to six medication groups for 1 week (n=10 per group): CH + 40% glycerin-water solution (1:1, wt/vol); CMCP; 2% CHX; CH + CMCP (1:1, wt/vol); CH + CMCP (2:3, wt/vol); and saline. Bacterial samples were collected and assayed for colony-forming units. After dentin blocks were split longitudinally, confocal laser scanning microscopy was used to assess the proportion of viable bacteria and EPS production in dentin. Results: CMCP exhibited the best antimicrobial activity, while CH was the least sensitive against E. faecalis (p<0.05). CHX showed similar antimicrobial properties to CH + CMCP (1:1, wt/vol) (p>0.05). CH combined with CMCP inhibited EPS synthesis by E. faecalis, which sensitized biofilms to antibacterial substances. Moreover, increasing concentrations of CMCP decreased EPS matrix formation, which effectively sensitized biofilms to disinfection agents. Conclusion: The EPS matrix dispelled by CH paste with CMCP may be related to its bactericidal effect; the visualization and analysis of EPS formation and microbial colonization in dentin may be a useful approach to verify medicaments for antimicrobial therapy.